Egg Incubation Temperature Affects Development of Innate Immune Function in Nestling American Robins (Turdus migratorius) - Merrill, Loren; Ospina, Emilie A.; Santymire, Rachel M.; Benson, Thomas J. (Physiological and biochemical zoology, 2020)
The innate immune system provides important first-line defenses against invading pathogens and is considered especially important for developing organisms. However, we know little about how early-life conditions influence these defenses in wild animals. For oviparous species such as birds, embryonic development occurs in the egg, which can be subject to variation in thermal conditions. There is evidence from cavity-nesting species and species with precocial young that reduced incubation temperatures can result in reduced measures of innate immunity. Whether and how this thermal variation impacts innate immunity for open-cup-nesting species with altricial offspring has not been examined. In this study, we experimentally manipulated egg incubation temperature for American robins (Turdus migratorius) and compared the bacteria-killing ability (BKA) of the nestlings’ blood plasma. We collected baseline and poststressor samples on day 7 and day 10 after hatch to gain additional insights into the ontogeny of this immune measure, as well as into whether any changes were linked to levels of the glucocorticoid hormone corticosterone (CORT). We found that nestlings incubated at the low treatment (36.1°C) had significantly reduced BKA compared with nestlings incubated at the high treatment (37.8°C) when controlling for the posthatch nest environment. We also documented a significant reduction in poststressor levels of BKA, as well as an increase in BKA from day 7 to day 10. We found a weak inverse association between CORT and BKA but no other indications that BKA was mediated via treatment-induced variation in CORT. Our results suggest that incubation temperature can affect development of innate immunity in open-cup-nesting passerines.